THE URGENCY OF IMPLEMENTING THE SUNSET CLAUSE IN THE FORMATION OF LEGISLATION IN INDONESIA TO PREVENT OVER-REGULATION - Asep Sapsudin (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2023)
This research is motivated by the phenomenon of overregulation in Indonesia, which has triggered hyperregulation, overlapping regulations, sectoral egos, and legal uncertainty, hampering the national investment climate. Conventional curative regulatory arrangements, such as the omnibus law method, are deemed incapable of addressing the root cause of regulatory overcrowding from the upstream. This research aims to analyze the urgency and formulate an ideal mechanism for institutionalizing sunset clauses (automatic expiration clauses) as a preventative solution to regulatory overcrowding. The research method used is normative juridical with a statute approach and a conceptual approach. Secondary data obtained through literature review was analyzed qualitatively and deductively. The results indicate that the adoption of sunset clauses is urgently needed in the Indonesian legislative system to automatically eliminate "zombie regulations" without a lengthy bureaucratic revocation process. Ideally, the institutionalization of a sunset clause would require an amendment to Law Number 12 of 2011 concerning the Establishment of Legislation (UU P3) as the primary legal umbrella, the establishment of a validity period (5–10 years) based on the Regulatory Impact Assessment (RIA) method, and strict exceptions to fundamental laws (human rights and constitutional law) to prevent legal vacuums. In conclusion, the sunset clause is a strategic instrument for restoring parliament's oversight function while simultaneously realizing a streamlined, adaptive, and responsive legal system.